A Study of the Water Quality of Rooftop Rainwater Collecting Systems (International Journal of Innovative Research in Engineering & Management, 2021)
Rooftop rainwater collecting as an alternative supply of drinking  water is gaining popularity, particularly in poor nations. The  existing data on the water quality of rooftop rainwater collecting  systems are reviewed in this article. The impact of several  variables on the physicochemical and microbiological quality of  collected water is addressed. Different contaminants in roof  runoff, such as heavy metals and trace organic pollutants, are  compared from different regions of the globe. The findings  indicate that the quality of water collected from roof catchments  often falls short of drinking-water standards. Unless specific  precautions are followed during rainwater collection and  storage, most studies show that collected water is highly  polluted microbiologically by a range of indicator and  pathogenic organisms. In certain instances, heavy metals and  trace organics may cause difficulties. The study concludes that  the cleanliness of rainwater collected from roofs should not be  taken for granted, and that the water should be analyzed for  microbial contamination in particular. To make the gathered  rainwater drinkable, it would need to be treated properly. The  study also highlights the need for further research into  appropriate design and management methods for roof-collected  rainwater sources to avoid contamination.
Keywords: Rainwater Harvesting; Rainwater Quality; Roof Catchments; Roof Runoff; Water Quality